KARAKTERISASI ENZIM PENDEGRADASI SENYAWA ASETONITRIL DALAM SEL Fusiarum solani AIII2 - YS Subowo (Research Center for Biology-Indonesian Institute of Sciences, 2003)
An acetonitrlie degrading-enzyme of Fusarium solani AIII2 from whole cells were studied. Decrease of acetonitrlie concentration and formation of it's degraded products were determined by gas chromatography. Ammonia analysis was done by Nessler's method. Fusarium solani AIII2 degraded 1% (v/v) acetonitrlie and produced acetic acid and ammonia. Acetonitrlie was degraded by nitrilase, with a rate of 0.903 mol min. mg dry weight cells. Maximum nitrilase activity of fusarium solani AIII2 was observed.